Green space for public mental health: an ethnographic study of ecotherapy in Wales. (May 2023) - Lord, E
Aims: In recent years, there has been a growing interest in the ways that human health intersects with exposure to nature. This article reports the findings of a research study investigating the experiences of people in South and West Wales who were engaged in a specific type of nature and health intervention: ecotherapy. Methods: Ethnographic methods were used to develop a qualitative account of the experiences of participants in four specific ecotherapy projects. Data collected during fieldwork included notes from participant observations, interviews with both individuals and small groups, and documents produced by the projects. Results: Findings were reported using two themes: 'smooth and striated bureaucracy' and 'escape and getting away'. The first theme focused on how participants negotiated tasks and systems related to gatekeeping, registration, record keeping, rule compliance, and evaluation. It was argued that this was experienced differently along a spectrum between striated, in which it was disruptive to time and space, and smooth, in which it was much more discrete. The second theme reported on an axiomatic perception that natural spaces represented an escape or refuge; in terms of both reconnecting with something beneficial in nature, and also disconnecting from pathological aspects of everyday life. In bringing the two themes into dialogue, it could be seen that bureaucratic practices often undermined the therapeutic sense of escape; and that this was more acutely experienced by participants from marginalised social groups. Conclusions: This article concludes by reasserting that the role of nature in human health is contested and arguing for a greater emphasis on inequities in access to good quality green and blue space. Specific interventions like ecotherapy need funding models that avoid striated bureaucratic processes, and the stress associated with these. Inclusive models of ecotherapy practice could contribute to public health goals related to population engagement with healthy environments.